Body Surface Area-Based Chemotherapy Dosing in a Pediatric Acute Lymphoblastic Leukemia Patient: A Detailed Case Report - Dr. Krithika Sri; Barath Raj.R; Sanjana B; Subanithi B; Stephy Ponnachan; Tharun D; Jisha Joe R. J (International Journal of Scientific Research in Science and Technology, 2025)
Acute Lymphoblastic Leukemia (ALL) is the most common childhood hematological malignancy, with a virtually 25% incidence of all cancers in children. Precise chemotherapy dosing in children is necessary to provide optimum efficacy without the occurrence of side effects. Among all the techniques used to determine the dose, dosing based on Body Surface Area (BSA) is the most optimal method in children, particularly for cytotoxic drugs with narrow therapeutic windows. This case report describes a 6-year-old girl who was diagnosed with precursor B-cell Acute Lymphoblastic Leukemia. With classic symptoms of weakness, pallor, and hepatosplenomegaly, the diagnosis was established using complete blood count, peripheral smear, bone marrow aspiration, and flow cytometry. The patient was categorized as standard risk and was treated with a modified Berlin-Frankfurt-Münster (BFM) regimen. Her body surface area (BSA) was calculated as 0.8 m² using the Mosteller formula, and chemotherapy agents such as vincristine, daunorubicin, dexamethasone, and L-asparaginase were administered based on this value. Supportive measures included hydration, prophylaxis for tumour lysis, antimicrobial therapy, and close monitoring of hematological and biochemical parameters. The patient tolerated induction well without major complications, such as mucositis or transient liver enzyme elevation. There were no episodes of febrile neutropenia, and remission was achieved on day 19 of treatment, indicating effective and well-tolerated induction. This case illustrates the applicability of BSA-based dosing in pediatric oncology by emphasizing the manner in which it offers a physiologically rational approach to dose calculation relative to weight-based dosing strategies. It also emphasizes the clinical value of formal treatment protocols, such as BFM, in resource-constrained settings. The report also considers emerging trends toward combining pharmacogenomics and therapeutic drug monitoring as a vehicle for further personalizing pediatric dosing regimens. In summary, this case reaffirms the continued applicability of BSA-based dosing as the standard for safe and effective pediatric chemotherapy.
Keywords: Pediatric Acute Lymphoblastic Leukemia; BSA-based Chemotherapy; Modified BFM Protocol; Vincristine; Chemotherapy Dosing; Pediatric Oncology